Healthy aging actions focused on functional ability - GAO Junling; BAO Zhijun (Guangxi Yike Daxue xuebao)
Healthy aging is one of the important strategies to cope with the challenge of global population aging. This paper systematically summarizes the causes and measures of healthy aging actions focused on functional ability, so as to provide some reference for the practice and research of healthy aging in our country.